A study on international mail volumes towards Pos Malaysia’s performance / Yuhanis Mohamed Noor - Mohamed Noor, Yuhanis (2010)
This study is focus on the declining international mail volumes issues at Pos Malaysia Berhad which has potential to affect company’s performance. The main objective of this project paper is identify the strategies taken by Pos Malaysia Berhad in order to address the issue of declining international mail volumes. The research is focusing on strategies taken by Pos Malaysia which is international business cooperation between Pos Malaysia and other Universal Postal Services (USPs) in order to stimulate growth of international mail volumes. This paper also identify the rationale of international cooperation established by the company as well as the effectiveness of the international business cooperation that been established for the past two years. Data collected and evidences are mainly from secondary data gathered from the company.